Rethinking capital structure and liquidity in technology firms: profitability as the key driver of financial performance - Serli Marcelina; Suhardi Suhardi; Mohamad Makrus (Lembaga Riset Mutiara Akbar (LARISMA), 2026)
This study aims to analyze the effect of capital structure, profitability, and liquidity on the financial performance of technology sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. Financial performance is measured using Return on Equity (ROE), while capital structure is proxied by Debt to Equity Ratio (DER), profitability by Return on Assets (ROA), and liquidity by Current Ratio (CR). This research applies a quantitative approach using panel data regression analysis. The selection of the panel data model was conducted through the Chow test, Hausman test, and Lagrange Multiplier test, resulting in the Random Effects Model as the most appropriate model. The findings reveal that profitability has a positive and significant effect on financial performance, indicating that efficient asset utilization contributes to higher shareholder returns. Meanwhile, capital structure and liquidity do not significantly affect financial performance. Simultaneously, the three independent variables also do not significantly explain variations in financial performance. The low coefficient of determination suggests that financial performance in technology companies is influenced by other factors beyond the research model, such as innovation, growth opportunities, and operational efficiency. These findings emphasize the importance of profitability as the primary driver of financial performance in technology firms.